Gaya Kepemimpinan Kepala Madrasah dalam Pembentukan Karakter Religius Peserta Didik (Input, Proses dan Output) - Helsi Arista; Ari Mariani; Devi Sartika; Deti Murni (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
School Management has more power for school administrators, namely the power to regulate and manage schools, to make decisions, regulate, direct, and control schools, so that school administrators are not arbitrary in administering schools, schools must be responsible for what they do to the community as a consequence of mad at provided by the public or society. So, accountability is very influential on public trust in the school, because it controls not only the school, but the community also participates in this matter. This research is field research conducted at Madrasah Tsanawiyah (MTs) Nurul Fatah Head of Curup. To obtain the required data or sources, the author uses qualitative research methods using a descriptive approach. This research was conducted using